Analisis Laju Pertumbuhan Karang Acropora sp. Hasil Transplantasi di Pantai Geger - Arimbi, Bunga Divia; Arthana, I Wayan; Ernawati, Ni Made (Current Trends in Aquatic Science; Vol 6 No 1 (2023), 2023)
Coral transplantation is one of the efforts to rehabilitate a damaged coral reefs. The successful growth of transplantation is influenced by water quality. This study aims to determine the relation between water quality parameters and the growth rates of Acropora sp. transplantation in Geger Beach. This research was conducted for 3 months during February until Aprils 2022, carried out in every 2 weeks at difference point. The observations was measuring length, width, high, and the increased of total corals fragment. The results showed the averages of length growth rate is 1.39 mm/2 weeks on each points. While the high growth rate on point 1 and 2 had a 0.14 mm/2 weeks different high, and each point had a values of 0.61 mm/2 weeks and 0.76 mm/2 weeks. On the width growth rate, each of point had a values of 2.06 mm/2 weeks and 1.50 mm/2 weeks, with 0.56 mm/2 weeks difference. The average of increased total corals fragment has the same growth, with 2 fragment at each point. The quality of waters in Geger Beach supported the growth of coral transplantation with temperatures ranging from 29.50-29.60 °C, brightness of 100%, depth of 0.97-1.1 m, currents of 0.16-0.18 m/s, salinity of 33.33-33.16‰, pH of 7.80-7.87, and DO of 6.27-6.29 mg/l. The results of Pearson’s test showed that waters parameters have correlations and significant relationship with the growth rates of Acropora sp., with all the values of signification is more than 0.05.